2004
DOI: 10.1021/jp047260d
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Structures of Amide Phospholipid Monolayers

Abstract: Monolayers of newly synthesized amide phospholipids, 1-O-hexadecyl-2-N-palmitoyl-2-amino-2-deoxy-snglycero-3-phosphocholine (L-ether-amide-PC) and 1-palmitoyl-2-N-palmitoyl-2-amino-2-deoxy-sn-glycero-3-phosphocholine (L-ester-amide-PC) were investigated at the air/subphase interface by Brewster angle microscopy combined with a conventional LB trough and Grazing incidence X-ray diffraction (GIXD). Both systems investigated exhibit two-dimensional domains with characteristic shape in the coexistence region betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…1,4 In chemistry, the phospholipid monolayer serves as an important building block for thin-film materials and smart surfaces. 5 With effective layer-by-layer Langmuir−Blodgett (LB) transfer, selfassembled monolayers have applications in wetting, adhesion, lubrication, and sensors. 6,7 In biology, the phospholipid monolayer can be loosely considered as a single leaflet of the biomembrane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,4 In chemistry, the phospholipid monolayer serves as an important building block for thin-film materials and smart surfaces. 5 With effective layer-by-layer Langmuir−Blodgett (LB) transfer, selfassembled monolayers have applications in wetting, adhesion, lubrication, and sensors. 6,7 In biology, the phospholipid monolayer can be loosely considered as a single leaflet of the biomembrane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As opposed to this, the critical temperatures of the monolayers differ significantly between AzidoPC ( T cr = 26.5 °C) and DPPC ( T cr = 44.1 °C) . Obviously, T m and T cr only correlate if both the fluid and the condensed phases are structurally comparable in the monolayer and bilayer, which is the case for DPPC . In the case of AzidoPC and PHPC, the lipids in bulk systems do neither form a regular rippled phase ( P β’ ) nor a bilayer gel phase ( L β or L β’ ).…”
Section: Resultsmentioning
confidence: 87%
“…30 Obviously, T m and T cr only correlate if both the fluid and the condensed phases are structurally comparable in the monolayer and bilayer, which is the case for DPPC. 35 In the case of AzidoPC and PHPC, the lipids in bulk systems do neither form a regular rippled phase (P β' ) nor a bilayer gel phase (L β or L β' ). Instead, they form an interdigitated gel phase (L β I), 5,6 which cannot exist at the air− water interface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Most previous studies of phospholipid phase transitions relied on the classical Langmuir film balance. It was found that there exists a significant hysteresis loop between the compression and expansion isotherms of phospholipid monolayers obtained with the Langmuir balance. The area enclosed in a π– A hysteresis loop represents the net loss of energy per compression–expansion cycle, which is a crucial biophysical property in evaluating the surface activity of pulmonary surfactant films . A good pulmonary surfactant film should enable reversible compression–expansion cycles that minimize the hysteresis area, thus consuming little to no energy in normal tidal breathing .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Because of losing monolayer materials from the air–water interface at the end of film compression, the subsequent expansion of the monolayer can hardly be reversible. Consequently, an evident hysteresis loop between the compression and expansion isotherms is usually observed with the Langmuir balance. This artifact of the Langmuir balance prevents the reversibility study of surface phase transitions.…”
Section: Introductionmentioning
confidence: 99%